Enhanced Acid Sphingomyelinase Activity Drives Immune Evasion and Tumor Growth in Non-Small Cell Lung Carcinoma - Kachler, Katerina; Bailer, Maximilian; Heim, Lisanne; Schumacher, Fabian; Reichel, Martin; Holzinger, Corinna D.; Trump, Sonja; Mittler, Susanne; Monti, Juliana; Trufa, Denis; Rieker, Ralf; Hartmann, Arndt; et al. (Cancer Research, 2017)
The lipid hydrolase enzyme acid sphingomyelinase (ASM) is required for the conversion of the lipid cell membrane component sphingomyelin into ceramide. In cancer cells, ASM-mediated ceramide production is important for apoptosis, cell proliferation, and immune modulation, highlighting ASM as a potential multimodal therapeutic target. In this study, we demonstrate elevated ASM activity in the lung tumor environment and blood serum of patients with non-small cell lung cancer (NSCLC). RNAi-mediated attenuation of SMPD1 in human NSCLC cells rendered them resistant to serum starvation-induced apoptosis. In a murine model of lung adenocarcinoma, ASM deficiency reduced tumor development in a manner associated with significant enhancement of Th1-mediated and cytotoxic T-cell-mediated antitumor immunity. Our findings indicate that targeting ASM in NSCLC can act by tumor cell-intrinsic and -extrinsic mechanisms to suppress tumor cell growth, most notably by enabling an effective antitumor immune response by the host. Cancer Res; 77(21); 5963-76. ©2017 AACR.
EVALuna2:4034